Integrative In Silico Characterization of Klotho Missense Variants rs9527025 and rs9536314: Structural Perturbation Prediction, Tissue Expression, and Functional Network Analysis - Bramadi Arya; Rita Maliza (Journal of Biotechnology and Natural Science, 2026)
The Klotho (KL) gene encodes a transmembrane protein that serves as an obligate co-receptor for fibroblast growth factor 23 (FGF23), regulating phosphate homeostasis, vitamin D metabolism, and aging-related signaling. The KL-VS haplotype carries two coding variants, rs9536314 (Phe352Val) and rs9527025 (Cys370Ser), with established contrasting functional effects: F352V impairs secretion through intracellular retention, while C370S enhances secretion. The structural basis of these opposing phenotypes remains uncharacterized, and non-KL-VS substitutions at position 370 from the multiallelic rs9527025 have not been computationally evaluated. This study presents an integrative in silico characterization of rs9527025 and rs9536314 in the KL1 domain of α-Klotho, combining multi-algorithm functional prediction, predicted thermodynamic perturbation analysis, tissue-specific expression profiling, and gene interaction network analysis. Results showed that rs9536314 substitutions consistently predicted greater functional damage and thermodynamic perturbation (ΔΔG up to -3.02 kcal/mol for F352V), consistent with disruption of the KL1 hydrophobic core as a structural basis for its secretion-impairing phenotype. For rs9527025, C370S (the KL-VS substitution) showed minimal predicted perturbation in line with its secretion-enhancing effect, while the uncharacterized C370Y and C370F substitutions showed inconsistent predictions suggesting more localized effects. GTEx analysis confirmed predominant KL expression in kidney cortex, contextualizing variant relevance in renal mineral metabolism. Network analysis identified KL as a central hub in the FGF23-FGFR signaling axis. These computational findings offer a structural interpretation that bridges predicted perturbations at residues 352 and 370 with their known contrasting functional effects on Klotho processing and secretion.